Effect of interface structure regulation caused by variation of imidization rate on conduction current characteristics of PI/nano-Al2O3 three-layer composite films - Xinyu Ma (Results in Physics, 2018)
A series of sandwich structure PI films were prepared by different imidization process, with pure PI film as the interlayer and PI/Al2O3 composite films as outer layers. The imidization rate of the film with different cured processes was calculated by characterizing by infrared spectrum (FT-IR), and the morphology of interlayer interface with different imidization rates by scanning electron microscope (SEM). When the imidization conditions of the first and second films were 260 °C/120 min, the composite films displayed better interface structure and higher imidization rate (ID) than others. Moreover, results also showed that the conduction current of three-layer composite film steadily improved with increased ID and temperature, and was higher than that of the pure film. At the temperature of 30 °C, the electrical aging threshold at different ID was obtained. When the ID reached the maximum value of 78.9%, the electrical aging threshold reached the maximum 41.69 kV/mm. Keywords: Polyimides, Composite films, Interfaces, Conduction current, Electrical degradation threshold